2014
DOI: 10.1186/s40529-014-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a SNARE protein AtBS14b alters BR response in Arabidopsis

Abstract: BackgroundN-ethyl-maleimide sensitive factor adaptor protein receptor (SNAREs) domain-containing proteins were known as key players in vesicle-associated membrane fusion. Genetic screening has revealed the function of SNAREs in different aspects of plant biology, but the role of many SNAREs are still unknown. In this study, we have characterized the role of Arabidopsis Qc-SNARE protein AtBS14b in brassinosteroids (BRs) signaling pathway.ResultsAtBS14b overexpression (AtBS14b ox) plants exhibited short hypocoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Overexpression of the AtBS14b caused insensitivity to exogenously applied BRs. AtBS14b directly interacts with the Membrane Steroid-Binding Protein1 (MSBP1) at vesicular compartments, but not with BRI1 or BAK1 [ 96 ]. The MSBP1 protein is localized in the plasma membrane and endosomes, and is able to bind the BR ligand.…”
Section: The Br Signalosome—an Updatementioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of the AtBS14b caused insensitivity to exogenously applied BRs. AtBS14b directly interacts with the Membrane Steroid-Binding Protein1 (MSBP1) at vesicular compartments, but not with BRI1 or BAK1 [ 96 ]. The MSBP1 protein is localized in the plasma membrane and endosomes, and is able to bind the BR ligand.…”
Section: The Br Signalosome—an Updatementioning
confidence: 99%
“…Transcription of the AtBS14b gene is down-regulated by BR in the BRI1-mediated process. AtBS14b acts via interacting with MSBP1 in the trans-Golgi network to enhance transport of MSBP1 to plasma membrane and its interaction with BAK1 [ 96 ] ( Figure 1 ).…”
Section: The Br Signalosome—an Updatementioning
confidence: 99%
“…They showed longer petioles, larger rosette diameters, less rosette leaves and slender shoots (Fig 5A and 5C and S2 Fig). We further observed the elongated hypocotyls in all these over-expressing lines (Fig 5B and 5D) [14]. Yet, they were all sensitive to BRZ (brassinozole) that specifically inhibits BR biosynthesis (Fig 5D and S3 Fig).…”
Section: Resultsmentioning
confidence: 82%
“…The YFP signals generated by GsCBRLK/GsBET11a co‐expression were mainly observed on the PM, as well as on some Golgi‐like punctate structures (Figure 1c). GsBET11a is homologous to AtBET11 (Figure 2a), which was suggested to be a Golgi‐located Qc‐SNARE (Bubeck et al ., 2008; Bolaños‐Villegas et al ., 2015), and AtBET12 was targeted at Golgi/TGN membranes (Bolaños‐Villegas et al ., 2015; Chung et al ., 2018) as well as the vesicular compartments surrounding the PM (Zhu et al ., 2014). In the present study, we showed that GsBET11a appeared in the Golgi/TGN‐like punctate structures and the PM (Figure 1e; Figure S1b), and this enabled its interaction with the PM‐located GsCBRLK (Yang et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%